PENINGKATAN PRESTASI BELAJAR MENCERITAKAN ISI HIKAYAT MELALUI PENERAPAN METODE INQUIRY-BASED LEARNING - Umi Indasyah (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2020)
The Difficulty learning Indonesian experienced by students of IX-D MTs Negeri 2 Mojokerto is reflected in the low value of daily tests about telling stories. In this classroom action research, the authors apply the inquiry-based learning method, so that the teaching and learning interactions can achieve the expected results. The application of the inquiry-based learning method in this research to improve student achievement in the material of telling story content in Indonesian language lessons begins with assigning students to observing the film trailer as shown in front of the class. Students record anything that happen in the saga. In advanced learning activities, students are given the task of compiling an outline of the saga that they have read or seen. Students compile a descriptive text from an essay framework that has been formed in their own language. Based on the results of the research, it shows the conclusion that the application of the inquiry-based learning method can improve student learning outcomes in the material of telling story content in Indonesian language lessons based on the post-test score which continues to increase from the first to the second cycle.